Tetracycline resistance and prevalence of tetracycline resistance genes in bacteria from marine aquaculture farms in Peninsular Malaysia - Thiang, Ee Lean; Chai, Stanley Choon Yip; Lee, Choon Weng; Takada, Hideshige; Wang, Ai Jun; Chai, Lay Ching; Bong, Chui Wei (Penerbit Universiti Kebangsaan Malaysia, 2022)
The indiscriminate use of antibiotic in aquaculture and leaching of antibiotic from aquaculture to the environment may led to the emergence and spread of antibiotic resistant bacteria and their resistant genes which is a public concern. Five tetracycline antibiotics (minocycline, doxycycline, chlorotetracycline, oxytetracycline and tetracycline) and 14 types of tetracycline genes, tet[(A), (B), (C), (D), (E), (G), (K), (L), (M), (O), (S), (P), (Q) and (X)], were investigated in waters from five marine aquaculture farms in Peninsular Malaysia. Tetracycline was detected in low concentrations from <LOQ to 25.6 ng/L. A total of 93 isolates of bacteria were isolated whereby Vibrio (n=29) and Pseudoalteromonas (n=7) were the predominant bacteria. Forty-eight of the isolates carried tet genes with 22.9% encoded multiple tet genes and 72.9% encoded a single tet gene. tet(A) (n = 20, 42%) was the most prevalent gene followed by tet(B) (n = 14, 29%) and tet(K) (n = 13, 27%). A few common tet carriers (Enterobacter, Vibrio, Photobacterium, and Pseudoalteromonas) carrying tet genes that have not been reported were identified. The values of the risk quotients (RQs) of tetracycline in Matang was 0.28 which posed a medium ecological risk to algae. Thus, the antibiotic residues in the aquaculture farm in Matang need to be monitored closely.